2007
DOI: 10.1590/s0037-86822007000300013
|View full text |Cite
|
Sign up to set email alerts
|

Isolamento e identificação de amebas de vida livre potencialmente patogênicas em amostras de ambientes de hospital público da cidade de Porto Alegre, RS

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…The present results showed that 50% of the samples (fresh water and dust) collected from a hospital environment in the Southern Brazil harbored potentially pathogenic species of Acanthamoeba (A. castellanii and A. polyphaga), representing a risk for patients and visitors. These data corroborated those of previous works developed in different Brazilian hospitals (Carlesso et al 2007;Texeira et al 2009;Carlesso et al 2010;Costa et al 2010), and emphasized the need for increasing the public awareness and hospital disinfection measures in order to reduce the incidence of Acanthamoeba infections (Carvalho et al 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present results showed that 50% of the samples (fresh water and dust) collected from a hospital environment in the Southern Brazil harbored potentially pathogenic species of Acanthamoeba (A. castellanii and A. polyphaga), representing a risk for patients and visitors. These data corroborated those of previous works developed in different Brazilian hospitals (Carlesso et al 2007;Texeira et al 2009;Carlesso et al 2010;Costa et al 2010), and emphasized the need for increasing the public awareness and hospital disinfection measures in order to reduce the incidence of Acanthamoeba infections (Carvalho et al 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless as observed in Table 1, five out of ten samples (50%) collected at community bathrooms of a public hospital (two fresh water and three dust samples) exhibited the presence of Acanthamoeba. Compared with other Brazilian studies, the prevalence of Acanthamoeba was lower than that obtained by the analysis of dust samples from a university hospital in Curitiba, PR (Costa et al 2010), but higher than that reported in the hospitals of Porto Alegre, RS (Carlesso et al 2007(Carlesso et al , 2010 and Santos, SP (Teixeira et al 2009). Considering the ubiquitous nature of Acanthamoeba, and the large number of factors that influenced their presence in a hospital environment, it was not surprising to obtain high but variable incidence of these protozoa.…”
Section: Discussioncontrasting
confidence: 56%
“…Its resistant form tolerates adverse environmental conditions, allowing it to survive in the various physical and chemical treatments, and arousing the interest of many researchers in the study of this amphizoic protozoan. Carlesso et al (2007) isolated and characterized amoebae of the genus Acanthamoeba and Naegleria in biofilms and dust, from a hospital in southern Brazil. In this study, the most prevalent genus found was Acanthamoeba.…”
Section: Discussionmentioning
confidence: 99%
“…After sedimentation for 5 minutes, 100 μL of each sample were spread over a plate of non-nutrient agar (PAS + 1.5% agar) containing a lawn of heat-killed Escherichia coli OP50. The plates were incubated at 25°C for 10–14 days and observed daily by light microscopy for the presence of amoeba cysts or trophozoites [15, 16]. Agar sections containing cysts or trophozoites were cut and transferred to new plates to enrich the cultures.…”
Section: Methodsmentioning
confidence: 99%